USAHA GURU PEMBIMBING MENGATASI MASALAH HUBUNGAN SOSIAL PESERTA DIDIK DALAM BELAJAR DI SMP N 4 SUTERA - Khairaty, Khairaty; Kasih, Fitri; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
The problem in this research is: How can a tutor attempt to overcome the problem of social relations students in learning in SMP N 4 SUTERA?, Views of: 1). Guidance counselor effort to overcome the problems experienced by students who are not accepted into the study, 2). Guidance counselor effort to overcome the problems experienced by students who tend to learn by themselves, 3). Guidance counselor effort to overcome the problems experienced by students who tend to choose friends in learning. This research is a descriptive study that attempted to portray the situation as it is. This study population is students of SMP N 4 SUTERA, a population of 428 people. Samples were selected by purposive random sampling technique, is the students who have problems in social relationships in learning. The tools used in data collection was a questionnaire and data analysis techniques using a percentage formula. The results are as follows: 1). Efforts to overcome problems guidance counselor experienced learners who are not accepted into the study were in the good category, 2) The guidance counselor to overcome the problems experienced by students who tend to learn on their own are in the good category, 3) The guidance counselor to overcome the problems experienced by the learners tend to choose friends who are learning the good category. Based on the above results the researchers to conclude that the business tutor solve social problems of students in SMP N 4 SUTERA can be categorized either. Here, the researchers suggested that a tutor to maintain and further enhance efforts to address problems of social relations students in learning and provide the kind of service that suits your needs and problems of learners.